$latex Df(x)=f'(x)=\frac{df}{dx}=\frac{d}{dx}f=\dot{f}(x) = \lim_{h \to 0}\frac{f(x+h)-f(x)}{h} $ Introduced in order to fix the idea of velocity: $latex v = \lim_{\Delta t \to 0}\frac{\Delta s}{\Delta t}=\frac{ds}{dt} $ See: Zeno's paradoxes Working example: $latex s(t) = At^3 + Bt + C$ $latex s + \Delta s = A ( t + \Delta t )^3 + B ( … Continue reading Derivatives


Sunday Afternoon TED Talks

 Stephen Wolfram: Computing a theory of everything Brian Cox on CERN's supercollider Patricia Burchat sheds light on dark matter Brian Greene on String Theory Jill Tarter's call to join the SETI search